Manufacturing and Society – A Freshman Introduction to Engineering Course with Manufacturing and Social Science Partnership (2020)
The curriculum and pedagogy of a freshman introduction to engineering course on manufacturing and society are presented. This course is designed to use the quadcopter drone as an example to teach knowledge in manufacturing processes and systems, illustrate potential impacts of manufacturing to society, and stimulate learning in innovation, teamwork, and communication in a real-world engineering environment. It is also designed to teach students how to best communicate their findings and conclusions. This course is built on two team-based projects. Students practiced and timed the assembly of a state-of-the-art drone, the DJI Spark, and created a mid-term project presentation and report of their plan to setup an assembly plant in Michigan for this drone. Students learned the assembly line design, cycle time balancing, time study, automation, robotics, ergonomics, process capability index, and plant layout. The final project is the design and manufacture of an attachment to a hobby drone, DJI F330, for a mission that will benefit society. Students learned the social-aspects of manufacturing, computer-aided design, additive manufacturing, fabrication skills, and manufacturing processes. Each team identified a societal need, designed an attachment to the DJI F330 drone, reviewed the design with experienced engineers, manufactured components, assembled the attachment, and evaluated them in drone test flights. This course was implemented in close collaboration with a local community college to share the lecture and lab materials as well as pedagogy in manufacturing to benefit the same cohort of high school graduates. This approach of integrated social science, manufacturing, and technical communication to teach manufacturing using drones and connect manufacturing and society were demonstrated to be effective for an introductory freshman engineering course. Freshman engineering students often experience tremendous changes and pressure in their first semester. The lecture, lab, and discussion session for communication were adjusted to help students’ transition in their first semester engineering study.